2020
DOI: 10.18632/aging.103257
|View full text |Cite|
|
Sign up to set email alerts
|

hsa_circ_0004018 suppresses the progression of liver fibrosis through regulating the hsa-miR-660-3p/TEP1 axis

Abstract: Efforts have been made in the prevention and treatment of liver fibrosis. The inhibition or depletion of the hepatic stellate cells (HSCs) has been considered as a potential approach. Recently, there are numbers of studies about the role of the circular RNA in the disease progression. However, the role of circular RNA in the regulation of HSCs and the progression of liver fibrosis remained elusive. In this study, we constructed a CCl4-induced liver fibrosis mouse model and overexpressed hsa_circ_0004018 in HSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 31 publications
(46 reference statements)
2
15
0
Order By: Relevance
“…Currently, more and more circRNAs are identified to act as crucial regulators in multiple pathological and physiological processes of many types of disease. Previous studies have showed that circRNAs can regulate the activation and proliferation of HSCs by usually acting as miRNA sponges, thus to involve in the process of liver fibrosis in liver failure (Ji et al., 2020 ; Li et al., 2020 ). In this study, we first investigated that circDIDO1 overexpression could suppress the proliferation, reduced pro-fibrotic markers α-SMA and collagen I, and induced apoptosis as well as cell cycle arrest in HSCs, thus repressing HSC activation.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, more and more circRNAs are identified to act as crucial regulators in multiple pathological and physiological processes of many types of disease. Previous studies have showed that circRNAs can regulate the activation and proliferation of HSCs by usually acting as miRNA sponges, thus to involve in the process of liver fibrosis in liver failure (Ji et al., 2020 ; Li et al., 2020 ). In this study, we first investigated that circDIDO1 overexpression could suppress the proliferation, reduced pro-fibrotic markers α-SMA and collagen I, and induced apoptosis as well as cell cycle arrest in HSCs, thus repressing HSC activation.…”
Section: Discussionmentioning
confidence: 99%
“…FBXW7 also prevented the ZFP36-mediated autophagy inactivation in isolated murine HSC by acting as a decoy to ZFP36, thus sensitizing the HSCs to a ferroptosis (a program of cell death) [172]. The last reported circRNA is the circ_0004018 that was reduced in the activated primary mouse HSCs [159]. In this study [159], circ_0004018 acts as a miR-660-3p sponge and causes the increase of Telomerase associated protein 1 (Tep1) expression.…”
Section: Circular Rnas and Hscsmentioning
confidence: 69%
“…The last reported circRNA is the circ_0004018 that was reduced in the activated primary mouse HSCs [159]. In this study [159], circ_0004018 acts as a miR-660-3p sponge and causes the increase of Telomerase associated protein 1 (Tep1) expression. Although the function of Tep1 in HSC activation is unknown, the increase of both circ_0004018 and Tep1 suppress HSC proliferation [159].…”
Section: Circular Rnas and Hscsmentioning
confidence: 72%
“…Telomeraseassociated protein 1 (TEP1), a component of telomerase and target of hsa-miR-660-3p [102], plays a key role in the development of liver fibrosis and cirrhosis [103]. Overexpression of hsa_circ_0004018, a sponge of hsa-miR-660-3p, increases the expression of TEP1 and significantly suppresses the proliferation and activation of HSCs [104]. Consistently, hsa_circ_0007874 (cMTO1) could inhibit HSC activation through sponging miR-181b-5p and miR-17-5p [105,106].…”
Section: Liver Fibrosis/cirrhosismentioning
confidence: 99%